Signaling Proteins That Regulate Spermatogenesis Are the Emerging Target of Toxicant-Induced Male Reproductive Dysfunction - Gao, Sheng; Wu, Xiaolong; Wang, Lingling; Bu, Tiao; Perrotta, Adolfo; Guaglianone, Giuseppe; Silvestrini, Bruno; Sun, Fei; Cheng, C. Yan (Frontiers in Endocrinology, 2021)
Abstract There is emerging evidence that environmental toxicants, in particular endocrine disrupting chemicals (EDCs) such as cadmium and perfluorooctanesulfonate (PFOS), induce Sertoli cell and testis injury, thereby perturbing spermatogenesis in humans and also widelife. Recent studies have shown that cadmium (e.g., cadmium chloride, CdCl2) and PFOS exert their disruptive effects through putative signaling proteins, similar to other pharmaceuticals, such as the non-hormonal male contraceptive drug adjudin. More important, these signaling proteins were also shown to be involved in modulating testis function based on studies in rodents. Collectively, these findings suggest that toxicants are using similar mechanisms to perturb Sertoli and testis function. These observations are physiologically significant, since a manipulation on the expression of these signaling proteins can possibly be used to manage the toxicant-induced male reproductive dysfunction. In this review, we highlight some of these findings and critically evaluate the possibility of future studies of using this approach to manage toxicant-induced defects in spermatrogenesis based on recent studies in animal models.